2013
DOI: 10.1093/gbe/evt001
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast Phylogenomics Indicates that Ginkgo biloba Is Sister to Cycads

Abstract: Molecular phylogenetic studies have not yet reached a consensus on the placement of Ginkgoales, which is represented by the only living species, Ginkgo biloba (common name: ginkgo). At least six discrepant placements of ginkgo have been proposed. This study aimed to use the chloroplast phylogenomic approach to examine possible factors that lead to such disagreeing placements. We found the sequence types used in the analyses as the most critical factor in the conflicting placements of ginkgo. In addition, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 68 publications
(89 reference statements)
5
52
2
Order By: Relevance
“…Analysis of molecular variance showed that 24 and 76% genetic variation existed within and among the populations of G. biloba, respectively. The Ginkgo genus represents an ancient evolutionary lineage within the gymnosperms (Wu et al, 2013), as demonstrated by extensive fossil findings from the Jurassic to the Tertiary periods in both the Northern and the Southern hemispheres (Zhou and Zheng, 2003;Zhou, 2009;Zhou et al, 2012). The novel polymorphic and monomorphic cpSSR markers developed in this study are useful for genetic studies of G. biloba, but they may also be important for determining the origin and evolutionary history of Ginkgo.…”
Section: Resultsmentioning
confidence: 78%
“…Analysis of molecular variance showed that 24 and 76% genetic variation existed within and among the populations of G. biloba, respectively. The Ginkgo genus represents an ancient evolutionary lineage within the gymnosperms (Wu et al, 2013), as demonstrated by extensive fossil findings from the Jurassic to the Tertiary periods in both the Northern and the Southern hemispheres (Zhou and Zheng, 2003;Zhou, 2009;Zhou et al, 2012). The novel polymorphic and monomorphic cpSSR markers developed in this study are useful for genetic studies of G. biloba, but they may also be important for determining the origin and evolutionary history of Ginkgo.…”
Section: Resultsmentioning
confidence: 78%
“…Cycadales and Ginkgoales clearly share various other archaic traits, such as motile sperm and asaccate sulcate pollen 12 . However, it is noteworthy that a Cycadales and Ginkgoales clade has been recovered repeatedly in some recent phylogenetic analyses of seed plants using nuclear 18S ribosomal (r)RNA sequences 41 , chloroplast genes 42 , amino acids 43 and in transcriptome analyses of land plants 44 .…”
Section: Nature Ecology and Evolutionmentioning
confidence: 99%
“…Phylogenetic relationships among cpDNA haplotypes were reconstructed using Bayesian inference implemented in MrBayes 3.1.2 (Ronquist and Huelsenbeck 2003) with Cycas taitungensis as the outgroup (Wu et al 2013; Gen-Bank accession No. NC_009618).…”
Section: Plastid Dna Sequence Analysesmentioning
confidence: 99%